ASESMEN SEBAGAI SALAH SATU BENTUK REHABILITASI BAGI PENCANDU NARKOBA - Putri, Rianda Prima (Ensiklopedia Sosial Review, 2019)
In general, assessments can be described as a process of obtaining information about clients comprehensively, both when the client starts the program, during the course of the program, to completion of the program. Information about clients is generally carried out with three approaches, namely observation, interviews, and medical examinations. The assessment is not only done at the BNN Rehabilitation Center / Office but can also be done at BNN representatives in the regions (BNNP and BNNK / City).